Research and Development Challenges Faced by Plant Factories to Solve Global Problems: From the Perspectives of Civilization and Culture - Toyoki Kozai; Hiroko Nakaoka; Na Lu; Duyen T. P. Nguyen; Eri Hayashi (Horticulturae, 2025)
This perspective paper examines the research and development challenges faced by plant factories with artificial lighting (plant factories hereafter). The global and local challenges facing our planet can be divided into the following four categories: (1) food and agriculture; (2) environment and ecosystems; (3) depletion, uneven distribution, and the overuse of nonrenewable resources; and (4) society, economy, and quality of life. All of the aspects of this four-way deadlock problem must be resolved simultaneously, since solving only one of them could exacerbate one or more of the remaining three. In this paper, the role of plant factories in solving the four-way deadlock problem is discussed from the following perspectives: (1) civilization and culture, (2) participatory science, and (3) the integration of biotechnology and the latest nonbiological technology, such as artificial intelligence (AI). The relationship and interactions between the environment and plant ecosystems are easily observed in the plant factories’ cultivation room. Thus, it is easy to analyze their relationship and interactions. The findings from such observations can also be applied to increase the yield in plant factories, with minimum resource inputs. Moreover, if the electricity generated by renewable energy sources is used, it will become an energy-autonomous plant factory. This means that the plant factory can be operated with the minimum contribution of greenhouse gas emissions to global warming and land area use.